Polymorphism of D-Loop Mitochondrial DNA Region and Phylogenetic in Five Indonesian Native Duck Population - Purwantini , Dattadewi; Yuwanta, Tri; Hartatik, Tety; Ismoyowati (International Journal of Poultry Science, 2012)
This research aimed to determine mitochondrial DNA (mtDNA) D-loop region polymorphism and phylogenetic in five Indonesian native ducks population namely Magelang duck, Tegal duck, Mojosari duck, Bali duck and Alabio duck. The significance of this research was applicable to conservation and refinement strategy as well as the improvement of genetic quality by utilizing the available native duck plasma nutfah. It further concerned with determining the genealogy of family, channel, breed or maternal inheritance that bred individuals in native duck population in Indonesia and discovering phylogenetic relations with Mallards duck (Anas platyrhynchos) and the other Anas ducks. Fragment of 718-bp was amplified by PCR and determined the nucleotide sequence of 701-bp. The sequence was then analyzed using Single Nucleotide Polymorphism (SNP) and compared to the standard nucleotide sequence from Anas Platyrhynchos complete genome (HM010684.1) in GenBank Accession. It obtained nucleotide percentage equation of 93.59±8.23%. Phylogenetic investigation used sequencing products and was analyzed using MEGA5 software. Indonesian native ducks have a relatively close genetic relationship with Anas Platyrhynchos and Anas zonorhyncha shown by the genetic distance varying from 0.000-0.786 compared to the other Anas ducks in the world (0.073-1.037) or to Cairina moschata (2.972-5.776). Highly distant genetic variation was found in Magelang duck compared to the other native ducks ranged from 0.000-0.950 to 0.000-0.312. The research concluded that polymorphism of mtDNA D-loop region was found in Indonesian native ducks and had relatively similar maternal inheritance with Anas platyrhyncos dan Anas zonorhyncha.